Efetividade do projeto Florestas Sociais: Semeando o Futuro - Moreira, Tiago [UNESP]; Fonseca, Renata Cristina Batista [UNESP]; Silva, Magali Ribeiro da [UNESP]; Siqueira, Alana Jessica Cruz [UNESP]; Ferreira, Álvaro Antônio de Almeida [UNESP]; Fabrin, Beatriz Papin [UNESP]; Ogawa, Cyndell Caram [UNESP]; Santos, Gabriel Francisco Delaqua dos [UNESP]; Silva, Gustavo Brichi da [UNESP]; Prosdocini, Helen de Matos [UNESP]; Coelho, João Francisco [UNESP]; Miranda, Letícia Paiva de [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
In the current context, we face a number of challenges related to awareness of the importance of valuation, preservation and protection of the environment and the sustainability of its resources. Environmental education becomes an important tool for thinking about how to change the way you think and act with respect to environmental issues, considering the present-day requirements. Thus, the project “Social Forestry: Sowing the future" aims to support the formation of citizens with ecologically sustainable attitudes, promoting society through conscious actions. The project began in 1996 and now works with children and youth participating in the Growing Project, a project that is linked to the Municipality of Botucatu. Children and youth participate in the project for a year and respond to the same questionnaire twice, once at the beginning and one at the end of the year; during dynamic and fun activities are developed with the intent to get their attention and make assimilate the information passed to them. Analysis of the questionnaire answered by the children and young people, both at the beginning and at the end of the year, shows that the highest percentage of mistakes focuses on fauna and flora issues, and that there was gain knowledge about environmental issues, by children, after passage through the project.

No contexto atual, enfrentamos uma série de desafios relacionados à conscientização da importância da valoração, preservação e proteção do meio ambiente e da sustentabilidade dos seus recursos. A educação ambiental torna-se uma ferramenta importante para a reflexão sobre como mudar a maneira de pensar e agir com relação às questões ambientais, considerando as exigências da atualidade. Sendo assim, o projeto “Florestas Sociais: semeando o futuro” tem por objetivo dar suporte na formação de cidadãos com atitudes ecologicamente sustentáveis, promovendo a sociedade através de ações conscientes. O projeto teve inicio em 1996 e hoje trabalha com crianças e jovens participantes do Projeto Crescer, um projeto que está vinculado a Prefeitura Municipal de Botucatu. As crianças e jovens participam do projeto por um ano e respondem a um mesmo questionário duas vezes, uma no inicio e outra no final do ano; durante o ano são desenvolvidas atividades dinâmicas e lúdicas com a intenção de chamar a atenção deles e fazer com que assimilem as informações passadas a eles. A análise do questionário respondido pelas crianças e jovens, tanto no começo quanto no final do ano, mostra que a maior porcentagem de erros se concentra nos temas fauna e flora, e que houve ganho de conhecimento sobre a questão ambiental, por parte das crianças, após passagem pelo projeto.
Keywords: Environmental education; Children; Extension; Educação ambiental; Crianças; Extensão